The Relationship Between Smartphone Addiction and Loneliness Among Students - Iffah Dewi Amalya; Alfiatur Rizqi; Ferdhika Amirul Fadjri (International Consortium of Education and Culture Research Studies, 2020)
This study aims to determine whether there is a relationship between smartphone addiction and a sense of pity among students of Sunan Ampel State Islamic University in Surabaya. Loneliness is the Y variable (the dependent variable), and smartphone addiction is the X variable (the independent variable). Research conducted on Sunan Ampel Surabaya State Islamic University students numbered 35 students in the category of adolescents with the number of 17 men and 18 women, increasing from ± 18 years and over who have smartphones. The data collection method used in this study is a Likert scale system that has been approved into five alternative answers. Data collection tools consist of a dimension of loneliness that was adapted by Gierveld and Tillburg (1990) consisting of 32 items and a smartphone addiction measuring device consisting of 18 items. Data analysis was performed by analyzing the implementation of product moments using the SPSS for windows version 16.0 assistance program. From the results of the analysis of research data obtained the relationship between smartphones and satisfaction with a significance level of p = 0.00, with the price of t = 5.45, this price is greater than t table of 0.361. Thus Ho was rejected and Ha was accepted, meaning there was a significant relationship between smartphone addiction and loneliness. This shows a significant difference to smartphone addiction for students.